Penampilan Reproduksi dan Perkembangan Skeleton Fetus Mencit Setelah Pemberian Ekstrak Buah Nanas Muda - Setyawati, Iriani (Jurnal Veteriner; Vol 12, No 3 (2011))
This experiment was performed to examine the effects of young pineapple (Ananas comosus) fruitextract on reproduction performance and foetus skeletal development given during organogenesis period.Twenty pregnant mice were randomly divided into four groups. The young pineapple fruit extract wastreated orally by gavage with doses 0% (control), 20%, 40%, and 80% since gestation day 6 to 15. Caesareansection were performed to pregnant mice on day 18 to remove foetuses. Observation covered : reproductionperformance (uterine weight before and after foetus removal), the foetus number (reabsorptions, dead/alive foetus), morphological of the foetus (weight and length of the litter, and malformations), and skeletaldevelopment (ossification number of metacarpus, metatarsus, vertebrae caudalis) and malformations ofcostae, sternebrae, and vertebrae. Statistical analysis was performed using Anova and Duncan’s MultipleRange Test.Teratogenic effects caused decreasing of earlier uterine weight and alive foetus, increasingdead foetus and hemorrhage, delayed skeletal ossification (decreasing ossification number of metacarpusand metatarsus) and caused costal malformation (intercostal fusion and convulated costal structure).Young pineapple fruit extract given to pregnant mice during organogenesis alter reproductive performancepregnant mice. The extract also caused morphological abnormalities (cretinism), hemorrhage, delayedossification on metacarpus and metatarsus, and costae malformation of the foetus.
Keywords: Ananas comosus, teratogenic, skeletal development